EQCM study of the [Au(III)Cl4](-)-[Au(I)Cl2](-)-Au(0) redox system in 1-ethyl-3-methylimidazolium tetrafluoroborate room-temperature ionic liquid - Oyama, Taku (Langmuir : the ACS journal of surfaces and colloids, 2010)
The electrochemical behavior of the [Au(III)Cl(4)](-)-[Au(I)Cl(2)](-)-Au(0) redox system in room temperature ionic liquid (RTIL) of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIBF(4)) has been investigated quantitatively using an in situ electrochemical quartz crystal microbalance (EQCM) technique based on a Pt film-coated quartz crystal electrode (Pt-QCE). A series of two-electron (2e) and one-electron (1e) reductions of the [Au(III)Cl(4)](-) to [Au(I)Cl(2)](-) and [Au(I)Cl(2)](-) to Au metal were recognized at the Pt surface. Besides, the disproportionation reaction of [Au(I)Cl(2)](-) (i.e., the 2e-reduction product of [Au(III)Cl(4)](-)) to [Au(III)Cl(4)](-) and Au metal was also observed. Electro-dissolution of the Au deposited on the Pt electrode through a 1e-oxidation reaction in the presence of chloride ions was also confirmed using the Pt-QCE based EQCM technique. A 2e-oxidation reaction of [Au(I)Cl(2)](-) (i.e., the dissolved product) to [Au(III)Cl(4)](-) along with the oxidation of Cl(-) ion on the Pt surface was also realized at high anodic potential. The results demonstrate that in situ EQCM technique is applicable and powerful in elucidating electrochemical surface phenomena accompanying a mass change in RTIL